2021
DOI: 10.17219/acem/135701
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of miR-15b partially reverses the cisplatin resistance of NSCLC through the GSK-3β/MCL-1 pathway

Abstract: Background. Induction of acquired drug resistance occurs frequently with cisplatin-based therapy for non-small cell lung cancer (NSCLC). As recent studies have demonstrated that deregulation of microRNAs (miRNAs) is associated with drug resistance in cancers, correcting the deregulation of miRNAs represents a promising strategy to reverse acquired resistance in NSCLC.Objectives. This study investigated the functional role of miR-15b in cisplatin resistance in NSCLC. Materials and methods.Cisplatin-resistant PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…MiR-15 was identified as an oncomir in various cancer types, including the NSCLC [ 47 ]. MiR-15b overexpression has been linked to cisplatin resistance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MiR-15 was identified as an oncomir in various cancer types, including the NSCLC [ 47 ]. MiR-15b overexpression has been linked to cisplatin resistance.…”
Section: Resultsmentioning
confidence: 99%
“…MiR-15b overexpression has been linked to cisplatin resistance. Anti-miR-15b notably restored cisplatin sensitivity in NSCLC cells [ 47 ] ( Table 2 ). The miR-15-16 cluster’s expression was limited by hypoxia, which supported tumour angiogenesis and metastasis [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that MCL1 is a key molecule in cisplatin resistance, such as. MCL1 in non-small cell lung cancer (NSCLC) ( Ma et al, 2016 ; Lu et al, 2021 ) and hypopharyngeal squamous cell carcinoma ( Liu X. et al, 2021 ). The miR-320a/MCL1 axis mediates the doxorubicin resistance of osteosarcoma ( Zhou et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: . References [ 25 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , ...…”
unclassified